2018
DOI: 10.1017/mor.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Labor Markets in the US and China: Social Capital andGuanxi

Abstract: Despite the major cultural and political differences between the United States and China, in both countries access to jobs is supposed to be guided by fair and equitable procedures. In the US, there is a presumption of an open labor market in which potential employees compete on the basis of their qualifications, where the fairness of decisions is guided by anti-discrimination laws and normative organizational policies. In China, although there is a history of close relationships that guide the exchange of fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 160 publications
2
23
0
Order By: Relevance
“…These findings are consistent with other empirical evidence in this journal that a firm's achievement is associated with large open networks (Burt & Burzynska, 2017; Burt & Opper, 2017; Zhao & Burt, 2018). These findings are also in line with broader sociological studies arguing for the importance of social connections (DiTomaso & Bian, 2018) and social capital generated by linking different communities within the social fabric of societies (Lin, Cook, & Burt, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…These findings are consistent with other empirical evidence in this journal that a firm's achievement is associated with large open networks (Burt & Burzynska, 2017; Burt & Opper, 2017; Zhao & Burt, 2018). These findings are also in line with broader sociological studies arguing for the importance of social connections (DiTomaso & Bian, 2018) and social capital generated by linking different communities within the social fabric of societies (Lin, Cook, & Burt, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…A TMT tends to select a new member who is similar to the team in function and experience. Indeed, research reveals that social connections emanating from a shared functional background are important in China because individuals tend rely on their own networks to recruit new firm members (DiTomaso & Bian, ). Similar to Colombo and Rabbiosi's () measure of technological similarity among different firms, we developed a measure of shared functional background to capture functional experience similarity among TMT members.…”
Section: Methodsmentioning
confidence: 99%
“…Socio-cultural demographic attributes such as gender, age, and educational level are easily noticed due to visual, accentbased, or class-based markers regardless of the situation (Hutzschenreuter & Horstkotte, 2013;Milliken & Martins, 1996). Socio-cultural differences tend to be associated with potentially conflicting societal values as well as with societal beliefs that may associate higher/lower status or competence to some social categories and not others (DiTomaso & Bian, 2018;DiTomaso, Post, & Parks-Yancy, 2007). For example, sociologists have long examined educational attainment or level as a social status feature, which is a source of feeling dissimilar from others with different educational levels (Andersson, 2018;Sewell & Hauser, 1972), while strategic management scholars have found that being different in terms of educational level from one's executive team increases the likelihood of turnover (Jackson et al, 1991).…”
Section: Relationship-related and Task-related Faultline-strength Ementioning
confidence: 99%
“…[ 1 ] To know what is Chinese, of course, one needs to know what is not Chinese, so comparative research is inherent in the mandate, and MOR has flourished as a source of quality comparative research on China (e.g., Batjargal, 2007a). To paraphrase a conclusion from DiTomaso and Bian's (2018) comparison of Chinese and US labor markets, the two countries come from different origins, and are steeped in different rhetoric, but have evolved to a similar condition of network connections providing competitive advantage for certain people and groups to secure more attractive positions and projects (cf. Boisot & Child, 1996; Peng, Lebedev, Vlas, Wang, & Shay, 2019 on ‘network capitalism’ in emerging markets).…”
Section: Introductionmentioning
confidence: 99%